Factors affecting parental refusal of lumbar puncture in Iraqi children in COVID-19 era: a cross-sectional study - Nabeeha Najatee Akram; Shurooq Talib Sadoon; Matheel Mohammed Jaafar; Wassan Nori (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the frequency and causes of parental lumbar puncture refusal for their children. Method: The cross-sectional study was conducted at the Central Child Teaching Hospital, Baghdad, Iraq, from October 1, 2021, to April 1, 2022, and comprised children aged at least >1 month at the emergency department wo had been advised to undergo lumbar puncture. Data from the mother of the child was collected using an interview-based questionnaire, exploring. demographic characteristics, the cause of lumbar puncture refusal, as well as knowledge of the advantages and risks of lumbar puncture. Data was analysed using SPSS 26. Results: There were 128 children with a mean age of 3.9±2.1 years (range: 1-120 months). The parents of 18(14%) patients refused the procedure, and the most frequent reason was fear of paralysis 12(67%). Refusal was significantly associated with mother’s age, parents’ levels of education, and parents’ knowledge of the risks of lumbar puncture (p<0.05). Conclusion: Raising public awareness and parents’ educational level regarding the necessity and safety of lumbar puncture procedure is vital to decrease the refusal rate and ensure a better health outcome. Key Words: Spinal Puncture, Demography, Paralysis, Fear